Chaos Control, Quad-Compound Anti-Synchronization, Analysis and Application on Novel Fractional Chaotic System - Khan, Ayub; Jahanzaib, Lone Seth; Trikha, Pushali (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper chaos control and synchronization techniques are applied on the introduced novel fractional chaotic systems. The system is extensively studied for its dynamical properties using various tools such as Lyapunov spectrum, bifurcation diagrams, phase portraits, equilibrium points, dissipative character, uniqueness of solution and so on. Besides the effect of changing fractional order on the dynamics are also studied in detail. The chaotic behavior of the novel system is controlled about any randomly chosen point. The systems are then synchronized in quad compound combination anti-synchronization with eight chaotic systems in presence of disturbances and uncertainties. The achieved synchronization is illustrated in secure communication with help of an example.